2006
DOI: 10.1348/147608305x69795
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive skin‐cutting: Parental bonding, personality and gender

Abstract: Although these results provide further confirmation of a potential association between prior trauma and repetitive skin-cutting, they rigorously challenge the validity of reported gender differences for this behaviour. Further, this study has identified that repetitive skin-cutting can arise independently of BPD and prior trauma. Clinical implications of these results and suggested directions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
2
18
0
3
Order By: Relevance
“…Deliberate self-harm behavior may occur in clinical as well as in nonclinical samples [9,10,[25][26][27]. DSM-IV and ICD-10 F list self-harm behavior as a diagnostic criterion of borderline personality disorder.…”
Section: Diagnostic Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Deliberate self-harm behavior may occur in clinical as well as in nonclinical samples [9,10,[25][26][27]. DSM-IV and ICD-10 F list self-harm behavior as a diagnostic criterion of borderline personality disorder.…”
Section: Diagnostic Classificationmentioning
confidence: 99%
“…Assessment categories: 1=no information; 2=case ascertainment/medical records; 3=standardized clinician-administered rating; 4=ad hoc interviews; 5=validated interviews; 6=single items, self-report/interview; 7=ad hoc questionnaire; 8=validated questionnaire (assignment to assessment category is given in parentheses if information is insufficient to judge). [23] LT (12 months) +++ Highest recurrence of DSH for age group 25-54 years Sex [11,26,27,49,52,67] CS 00/(++) 6 studies found no sex differences in adults [107] 1 study found more females among medical patients treated for self-harm [45,87,92,93,102,109,110] 6 studies on adolescents found a higher prevalence in females (2:1 to 4:1); 1 study on adolescents found no sex differences [69] LT (1-2 years) 000 Not predictive of DSH recurrence [23] LT (12 months) Unemployment [78,99] CS +++ [90] LT (6 months) Predictive of DSH recurrence [23] LT (12 months) No partnership [78] CS +++ [90] LT (6 months) Predictive of DSH recurrence (except when widowed) [23] LT (12 months factor. "+" indicates positive evidence from only one crosssectional study.…”
Section: Taxonomy Of Correlates and Risk Factorsmentioning
confidence: 99%
“…4 9,50 However, self-cutting can also arise de novo without any overt history of trauma or borderline personality disorder. 51 Nevertheless, the type of self-harm does not necessarily identify the seriousness of the underlying psychopathology. Cryole, for example, studied 280 college undergraduates and noted that 31% had "minor" self-harming behavior characterized by skin picking or fingernail biting over the previous three years; 20% had "major" selfinjurious behavior with self-cutting and self-burning.…”
Section: Etiology Of Deliberate Self-harmmentioning
confidence: 99%
“…Some authors have concluded that the incidence for both genders is similar Gratz, Conrad, & Roemer, 2002;Klonsky, Oltmanns, & Turkheimer, 2003;Marchetta, 2006;Nock et al, 2006;Swadi, 2004;Tyler, Whitbeck, Hoyt, & Johnson, 2003;White et al, 2002). Other authors report that the behavior occurs more frequently among females than males Laye-Gindhu & Schonert-Reichl, 2005;Levenkron, 1998;Shaw, 2002).…”
Section: Incidence Of Sfmentioning
confidence: 99%
“…Past traumatic experiences are often present in the lives of those who practice SI (Derouin & Bravender, 2004;Marchetta, 2006;Shaw, 2002;Skegg, 2005; ). Many of these traumatic experiences relate to child abuse and subsequent post traumatic stress Cavanaugh, 2002;Derouin & Bravender, 2004;Gratz & Chapman, 2007;Gratz, Conrad, & Roemer, 2002;Nixon, Cloutier, & Aggarwal, 2002;Polk & Liss, 2007;Strong, 1998;Suyemoto & MacDonald, 1995;Swadi, 2004;Tyler et al, 2003;Walsh, 2006;White et al, 2002; ).…”
Section: Childhood Trauma and Post Traumatic Stressmentioning
confidence: 99%